Desenvolvimento inicial de plantas de milho em solo fertilizado com fosfatos e biofertilizante líquido - Carapeba, Gabriel Augusto Sgobi Ferreira (Universidade Federal de São Carlos, 2025)
The growing demand for phosphate fertilizers and the depletion of their non-renewable mineral sources pose crucial challenges to agricultural sustainability. Phosphorus (P) is vital for plant development, and biofertilizers containing P-solubilizing microorganisms are a promising alternative to optimize P availability in the soil and reduce dependence on mineral inputs. This study evaluated the influence of different P sources and a liquid biofertilizer on the growth and physiological parameters of corn (Zea mays) in a greenhouse. We analyzed plant height, shoot dry matter, chlorophyll content, and physiological indicators, including stomatal conductance, transpiration, photosystem II quantum efficiency, electron transport rate, and leaf temperature. The results showed that phosphates with higher solubility, such as Triple Superphosphate (TSP) and a Phosphate Mixture (PM), significantly promoted initial growth and biomass accumulation. In contrast, the biofertilizer had only a limited positive impact on plant height at the initial stage (12 days after emergence) and showed no significant effects on other variables or later development stages, nor did it exhibit synergy with natural rock phosphates (GAFSA and FNN). We conclude that soluble P sources are critical for establishing initial crop vigor. The effectiveness of the tested biofertilizer seems dependent on application conditions and plant stage, highlighting the need for future research on optimal doses and application strategies to unlock its full potential.
Initial development of maize plants in soil fertilized with phosphates and liquid biofertilizer
Keywords: Fósforo; Fertilizantes; Fosfatos; Microrganismos; Milho; Eficiência; Phosphorus; Fertilizers; Phosphates; Microorganisms; Corn; Efficiency; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA; 12. Consumo e Produção Responsáveis